A Comparative Study of Old English Metre - Whitman, F. H. (Book collections on Project MUSE., 1993)
Ancient Germanic, Celtic, and Italic verse seem to be related. Frank Whitman points out that not only is the language within these traditions stressed and very different from other ancient Indo-European languages, but also the metrical principles underlying the verse of these three stressed languages differ demonstrably from those found elsewhere. Whitman begins with an analysis of Italic verse because it is far older than that of German or Celtic traditions, and is therefore more likely to yield primitive metrical patterns common to all three. After analysing the dominant pattterns of the earliest accentual verse, he turns to Old English metre, and looks closely at the typical length of the halflines, the phenomenon of clashing stress, and the nature of light lines. In his conclusion he introduces a new paradigm for the description of Old English metre.